1953
DOI: 10.1002/jps.3030420419
|View full text |Cite
|
Sign up to set email alerts
|

Esters of Gentisic Acid and Their Toxicities**

Abstract: The acute toxicities of thirteen new esters of gentisic acid and that of gentisic acid have been determined by the intravenous injection of the com unds into white mice. The results are integrated by Behren's method. The 3 -~t h y l a m i n o p r o p y I esters of gentisic acid are more toxic generally than the 2-diethylaminoethyl counterparts. The 3-diethylaminopropyl-5-methoxy salicylate hydrochloride is the most toxic of the new esters. The increase in toxicity of the hydrochlorides of the esters of gentisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1981
1981
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…47 Due to the presence of a carboxylic group on the aromatic nucleus, gentisic acid has a surprisingly low toxicity, unlike other phenols. 48,49 According to a chemical vendor, Science Lab.com, DHB has an acute oral toxicity in mice (LD50: a dose causing death in 50% of the animals) of 4500 mg/kg (http://www.sciencelab.com/xMSDS-2,5-Dihydroxybenzoic_Acid-9923770) comparable to the LD50 of 4000 mg/kg for sea salt NaCl (http://www.sciencelab.com/ msds.php?msdsId)9927593). DHB is also used in dermocosmetic formulations to stimulate the process of epidermal renewal and nontherapeutic skin treatment of wrinkles, fine lines, and blemishes of the skin (http://www.freepatentsonline.com/5766613.html).…”
Section: Analysis Of Mouse Pituitary Peptides By Maldi-tof Msmentioning
confidence: 99%
“…47 Due to the presence of a carboxylic group on the aromatic nucleus, gentisic acid has a surprisingly low toxicity, unlike other phenols. 48,49 According to a chemical vendor, Science Lab.com, DHB has an acute oral toxicity in mice (LD50: a dose causing death in 50% of the animals) of 4500 mg/kg (http://www.sciencelab.com/xMSDS-2,5-Dihydroxybenzoic_Acid-9923770) comparable to the LD50 of 4000 mg/kg for sea salt NaCl (http://www.sciencelab.com/ msds.php?msdsId)9927593). DHB is also used in dermocosmetic formulations to stimulate the process of epidermal renewal and nontherapeutic skin treatment of wrinkles, fine lines, and blemishes of the skin (http://www.freepatentsonline.com/5766613.html).…”
Section: Analysis Of Mouse Pituitary Peptides By Maldi-tof Msmentioning
confidence: 99%
“…2,5-DHB inhibits the polymorphonuclear blood leukocytes aggregation and hyaluronidase in human blood effectively, while SA and ASA are significantly less effective. It has been reported that in the case of high fever conditions, the excretion of 2,5-DHB is remarkably increased in urine as compared to SA [6][7][8][9][10][11]. About 60% of SA remains unmetabolized in the human systems and reacts with OH free radical to produce 2,3-DHB and 2,5-DHB.…”
Section: Introductionmentioning
confidence: 97%